2021
DOI: 10.1103/physrevb.103.205125
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of the quantum fluctuation driven amplitude mode in a microcavity polariton condensate

Abstract: The Higgs amplitude mode is a collective excitation studied and observed in a broad class of matter, including superconductors, charge density waves, antiferromagnets, 3 He p-wave superfluid, and ultracold atomic condensates. In all the observations reported thus far, the amplitude mode was excited by perturbing the condensate out of equilibrium. Studying an exciton-polariton condensate, here we report the first observation of this mode purely driven by intrinsic quantum fluctuations without such perturbations… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…However, these predictions have yet to be confirmed experimentally, and indeed it has recently been shown that any such modifications occur at momenta that are too low to be directly resolved in high-quality microcavities [34]. Furthermore, while the observed shape of the Bogoliubov spectrum in experiments has so far appeared to be consistent with conventional Bogoliubov theory [34][35][36][37][38][39][40][41][42][43], there are notable unexplained observations such as the recently measured occupations of the excitation branches [41].…”
Section: Introductionmentioning
confidence: 97%
“…However, these predictions have yet to be confirmed experimentally, and indeed it has recently been shown that any such modifications occur at momenta that are too low to be directly resolved in high-quality microcavities [34]. Furthermore, while the observed shape of the Bogoliubov spectrum in experiments has so far appeared to be consistent with conventional Bogoliubov theory [34][35][36][37][38][39][40][41][42][43], there are notable unexplained observations such as the recently measured occupations of the excitation branches [41].…”
Section: Introductionmentioning
confidence: 97%
“…Condensate depletion by interactions has recently gained significant experimental attention [72][73][74][75][76]. Relatedly, BdG modes are used to renormalize phonon-assisted photoluminescence line shapes, e.g.…”
mentioning
confidence: 99%